ANALISIS SISTEM INFORMASI AKUNTANSI PENGELUARAN KAS ATAS PENGAJUAN PEMBAYARAN PADA PT PELNI (PERSERO) CABANG SURABAYA - Anjani, Amelia Berliana Dwi; Munari Munari (Jurnal Ilmiah Manajemen dan Akuntansi, 2025)
The rapid advancement of information technology has encouraged companies to transition to digital systems in managing their finances, one of which is through the implementation of accounting information systems. This study aims to examine the implementation of an Oracle-based accounting information system in managing cash disbursements at PT PELNI (Persero) Surabaya Branch, as well as to evaluate the effectiveness of the internal controls in place. The research uses a descriptive qualitative approach with a case study method based on direct field observations conducted during an internship program. The findings reveal that the use of the Oracle system significantly accelerates the recording of cash transactions and provides accurate and real-time financial data. Internal control practices such as segregation of duties, document verification, and periodic audits play a vital role in ensuring the security and accountability of transactions. However, challenges still exist, including incomplete supporting documents and limited network infrastructure. Therefore, improving human resource competencies and upgrading technological systems are essential strategies to enhance efficiency and transparency in the company’s financial operations